2022
DOI: 10.3389/fmicb.2022.959901
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and spatial-temporal clustering of visceral leishmaniasis in mainland China from 2019 to 2021

Abstract: BackgroundVisceral leishmaniasis (VL) is a serious vector-borne disease in central and western China. In recent years, the number of VL cases increased gradually, particularly the mountain-type zoonotic visceral leishmaniasis (MT-ZVL). This study clarified the epidemiological features and spatial-temporal clustering of VL in China between 2019 and 2021, identified the risk areas for VL transmission, and provided scientific evidence for the prevention and control of VL.Materials and methodsThe information on VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Thus, MT-ZVL was closely related to topography and the persistence of the natural habitat of MT-ZVL makes it difficult to prevent the transmission of MT-ZVL in such areas [ 38 ]. In recent years, with increases in global warming, the gradual improvement of the natural ecological environment, coupled with the implementation of ecological protection policies such as returning farmland to forests in China, the population density and distribution of wild host reservoirs and sandflies have gradually been restored, the infection rate of dogs has increased, and MT-ZVL has reemerged in previously-endemic counties [ 39 , 40 ]. Surveillance studies showed that MT-ZVL re-emergence occurred in areas with hilly topographies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MT-ZVL was closely related to topography and the persistence of the natural habitat of MT-ZVL makes it difficult to prevent the transmission of MT-ZVL in such areas [ 38 ]. In recent years, with increases in global warming, the gradual improvement of the natural ecological environment, coupled with the implementation of ecological protection policies such as returning farmland to forests in China, the population density and distribution of wild host reservoirs and sandflies have gradually been restored, the infection rate of dogs has increased, and MT-ZVL has reemerged in previously-endemic counties [ 39 , 40 ]. Surveillance studies showed that MT-ZVL re-emergence occurred in areas with hilly topographies.…”
Section: Discussionmentioning
confidence: 99%
“…donovani [ 8 ]. It has been effectively controlled after decades’ effort of case treatment and vector control in the most area of China [ 8 , 9 ], currently with only around 250–300 new cases reported annually in the northwest desert areas based on WHO Global Health Observatory [ 10 ] and other studies [ 11 , 12 ]. CL is barely seen in China, with sporadic cases reported in the Gobi desert area of west China, mainly caused by L .…”
Section: Introductionmentioning
confidence: 99%
“…Even though most of CL is self-healing over 3 months to 5 years depending on the infected species, up to 10% of them progress to more severe manifestations called mucocutaneous leishmaniasis [1,6,7] In China, VL was one of the most serious parasitic diseases and seriously endemic in 16 provinces in 1950s transmitted by the bite of sandfly carrying promastigote of L. donovani [8]. It has been effectively controlled after decades' effort of case treatment and vector control in the most area of China [8,9], currently with only around 250-300 new cases reported annually in the northwest desert areas based on WHO Global Health Observatory [10] and other studies [11,12]. CL is barely seen in China, with sporadic cases reported in the Gobi desert area of west China, mainly caused by L. infantum, the species believed to be circulated in local animals [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemics of VL have remained low in the 21st century. Nevertheless, the number of MT-ZVL cases reported in central China has rapidly increased and the geographic coverage of MT-ZVL epidemics has quickly expanded, with patients found predominantly in the Loess Plateau and its extensions, including Gansu, Shanxi, Shaanxi, Sichuan and Henan provinces [10][11][12]. Shanxi province has been historically endemic for MT-ZVL, with the most cases of MT-ZVL reported re-emergence of this subtype [13].…”
Section: Introductionmentioning
confidence: 99%